A modified cement slurry composite additive for mining and its preparation method and application
By developing a composite additive for mineral modified cement slurry containing modified water reducer, bentonite and modified microcapsules, the problems of soft deformation and slip deformation of surrounding rock are solved, the self-healing ability and compressive strength of cement grouting materials are improved, and the high performance needs of mines are met in the high temperature environment.
Patent Information
- Application Number
- CN202410967355.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-07-18
AI Technical Summary
During the mining process of mine, the surrounding rock has severe soft deformation and slip deformation, resulting in difficulty in supporting the well and tunnel engineering. The existing polycarboxylic acid water reducing agent has poor dispersion in concrete, making it difficult to effectively improve the mud resistance and self-healing ability of cement grouting materials.
A composite additive for mineral modified cement slurry is developed, including modified water reducer, bentonite, polymer aluminum sulfate, polymer aluminum chloride, calcium sulfate, hydroxypropyl methylcellulose and modified microcapsules. The modified microcapsules are coated with toluene diisocyanate by modifying polypropylene to improve their dispersion and thermal stability in cement slurry.
It improves the crack self-healing ability and compressive strength of cement grouting materials, enhances the material's high temperature resistance and UV aging resistance, and meets the high performance needs of mineral reinforcement slurries.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of mining grouting materials, and in particular to a mining modified cement slurry composite additive and a preparation method and application thereof. Background Art
[0002] With the increase of mining depth, the surrounding rock of the mine shows obvious soft rock deformation characteristics, and the sliding deformation movement of the surrounding rock becomes more and more intense, making the support of the mine engineering more difficult. With the development of grouting technology, full-section grouting has become one of the effective and important means of surrounding rock reinforcement, water interception and plugging, and geological structure control engineering. Cement concrete materials, which are usually used as cementitious materials, sand and stone as aggregates, and mixed with water and additives in a certain proportion, are widely used in mining grouting materials. Additives used in cement concrete materials include water reducers, retarders, early strength agents, quick setting agents, antifreeze agents, etc. Polycarboxylate water reducer is an important component of high-performance concrete now. The montmorillonite layered structure contained in the soil entrained in the sand and gravel of concrete will adsorb the long side chains of polycarboxylate water reducer, significantly reduce the dispersibility of polycarboxylate water reducer in concrete, and reduce the use effect. The expected effect can only be achieved by increasing the amount of water reducer, but it increases the cost. Developing a suitable modification method to improve the anti-mud properties of polycarboxylate water reducer is a direction worth studying at present.
[0003] Previous studies have used microcapsules formed by polypropylene coating toluene diisocyanate to improve the self-healing ability of concrete cracks, which is suitable for the reinforcement and treatment of rock cracks in coal mines. However, the working environment temperature in coal mines is very high, and the polypropylene molecular chain lacks active functional groups, and the surface is hydrophobic and has low surface energy. It is not easy to disperse in cement slurry. The thermal stability and aging resistance of polypropylene are also poor. In order to improve the performance of the microcapsule, it is necessary to further modify the polypropylene so that the modified microcapsule can better meet the use requirements of mining reinforcement slurry. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a composite additive for modified cement slurry for mining, and a preparation method and application thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A modified cement slurry composite additive for mining, comprising the following components in parts by weight: 2-4 parts of modified water reducing agent, 4-6 parts of bentonite, 1-2 parts of polyaluminium sulfate, 0.5-1 parts of polyaluminium chloride, 4-6 parts of calcium sulfate, 0.5-0.7 parts of hydroxypropyl methylcellulose, 0.6-0.8 parts of modified microcapsules, and 25-35 parts of water;
[0007] The preparation of the modified cement slurry composite additive for mining comprises the following steps:
[0008] Add modified water reducing agent, bentonite, polyaluminum sulfate, polyaluminum chloride, calcium sulfate, hydroxypropyl methylcellulose and modified microcapsules into water in sequence and stir for 20-30 minutes to obtain a composite additive for modified cement slurry for mining.
[0009] The modified microcapsule is prepared by the following steps:
[0010] Step A1: 4-bromo-2-nitroaniline, concentrated hydrochloric acid and water are added to a flask, stirred at 30°C for 30 minutes, and then cooled to 0°C in an ice-water bath. Sodium nitrite solution is slowly added dropwise to the flask, and the reaction is stirred for 20-30 minutes to obtain a reaction solution, and urea is added until the reaction solution turns starch-potassium iodide test paper blue to obtain a diazonium salt intermediate; isoeugenol and methanol are then added to a three-necked flask, and sodium carbonate is added to adjust the pH to 7.5-8.5. The diazonium salt intermediate is slowly added dropwise within 45-60 minutes while stirring in an ice-water bath, and the reaction is continued with stirring for 2-2.5 hours to obtain a diazo product;
[0011] Further, the dosage ratio of 4-bromo-2-nitroaniline, concentrated hydrochloric acid, water, and sodium nitrite solution is 0.032 mol: 8 mL: 4 mL: 45-55 mL, the mass fraction of concentrated hydrochloric acid is 36.5%, and the concentration of sodium nitrite solution is 1 mol / L; the dosage ratio of isoeugenol, methanol, sodium carbonate, and diazonium salt intermediate is 0.016 mol: 80-90 mL: 0.005-0.010 mol: 0.016 mol;
[0012] During the reaction of step A1, 4-bromo-2-nitroaniline first reacts with concentrated hydrochloric acid and sodium nitrite to generate a diazonium salt intermediate, and the diazonium salt intermediate then adds to the ortho position of the phenolic hydroxyl group on the benzene ring of isoeugenol to generate a diazo product;
[0013] Step A2: Add the diazo product, ethanol and sodium hydroxide into a three-necked flask, heat to 65-75°C, start reflux stirring, then add an equal amount of sodium dithionite three times, reflux stirring and react for 1-1.5h, cool to room temperature, add hydrochloric acid to adjust the pH to 5-6, filter, wash the filter cake with anhydrous ethanol, and dry to obtain bromoaryl hydrocarbon;
[0014] Further, the dosage ratio of the diazo product, ethanol, sodium hydroxide and sodium dithionite is 0.1 mol: 115-125 mL: 0.02-0.05 mol: 0.2-0.3 mol; the volume fraction of ethanol is 95%;
[0015] During the reaction of step A2, under the reduction of sodium dithionite, the azo group on the benzene ring in the diazo product and the nitro group adjacent to the azo group are ring-closed to form a benzotriazole ring, thereby obtaining a brominated aromatic hydrocarbon containing a benzotriazole ring and a terminal carbon-carbon double bond;
[0016] Step A3: Add bromoaryl hydrocarbon, 3-aminopropylpentamethyldisiloxane and methanol into a flask, add 2-dicyclohexylphosphine-2'-4'-6'-triisopropylbiphenyl, tris(dibenzylideneacetone)dipalladium and potassium carbonate, reflux and stir at 80°C under nitrogen protection for 4-5h, and vacuum dry at 50°C to obtain a functional monomer;
[0017] Further, the amount ratio of bromoaryl hydrocarbon, 3-aminopropylpentamethyldisiloxane, methanol, 2-dicyclohexylphospho-2'-4'-6'-triisopropylbiphenyl, tris(dibenzylideneacetone)dipalladium and potassium carbonate is 0.12 mol: 0.06 mol: 135-145 mL: 0.0025 g: 0.0025 g: 0.15-0.18 mol;
[0018] During the reaction of step A3, the bromoaryl hydrocarbon and 3-aminopropylpentamethyldisiloxane undergo a debromination and hydrobromination coupling reaction to generate a functional monomer containing a terminal carbon-carbon double bond;
[0019] Step A4: In a nitrogen atmosphere, toluene, functional monomers and crosslinking agents were added to the reaction bottle, and after stirring for 10-15 minutes, polypropylene was added and stirred for another 10-15 minutes. The reaction bottle was sealed and then 60 After irradiating with Coγ-rays for 8-10 hours, the polypropylene is taken out, and the taken out polypropylene is rinsed with anhydrous ethanol, extracted with acetone, and dried to obtain modified polypropylene; the modified polypropylene is placed in a flask and heated to 160°C, stirred for 30 minutes, and then toluene diisocyanate is added, the temperature is maintained at 160°C, and stirring is continued for 2 hours, and then perfluorotributylamine is quickly added at a stirring speed of 600r / min and cooled to obtain a suspension, the suspension is dispersed with ultrasound for 30 minutes, filtered, and placed in a 60°C oven for drying for 24 hours to obtain modified microcapsules.
[0020] Further, the dosage ratio of toluene, functional monomer, crosslinking agent and polypropylene is 400-450mL: 10-15g: 7-9g: 100-110g, the crosslinking agent is divinylbenzene; the dosage ratio of modified polypropylene, toluene diisocyanate and perfluorotributylamine is 10-15g: 20-30g: 15-25g;
[0021] During the reaction of step A4, 60 Under the irradiation of Coγ-rays and the assistance of a cross-linking agent, the functional monomer is grafted onto polypropylene to obtain modified polypropylene; then the modified polypropylene is coated with toluene diisocyanate by a melt dispersion condensation method to obtain modified microcapsules.
[0022] The modified water-reducing agent is prepared by the following steps:
[0023] Step B1: Add dihydroxy-terminated polydimethylsiloxane to a flask, introduce nitrogen, heat to 70-80°C, stir for 30 minutes, then add hydroquinone, triethylamine and maleic anhydride, heat to 80-90°C, stir for 4-5 hours, and obtain reaction product a; In a nitrogen atmosphere, add reaction product a to a round-bottom flask, heat to 45°C, add tetrabutylammonium bromide, start stirring, slowly add epichlorohydrin dropwise to the round-bottom flask, stir and react for 5-6 hours, and obtain reaction product b;
[0024] Further, the usage ratio of bishydroxy-terminated polydimethylsiloxane, hydroquinone, triethylamine and maleic anhydride is 50g:0.04g:2.49g:19.6g; the usage ratio of reaction product a, tetrabutylammonium bromide and epichlorohydrin is 20-25g:0.001-0.0012mol:0.1mol;
[0025] During the reaction process of step B1, the dihydroxy-terminated polydimethylsiloxane reacts with maleic anhydride to undergo a monoesterification reaction to generate maleic anhydride monoalcohol ester, namely, reaction product a; the reaction product a then undergoes a ring-opening reaction with epichlorohydrin to generate a ring-opening product, namely, reaction product b.
[0026] Step B2: In a nitrogen atmosphere, add the reaction product b and phenylalanine into a flask, raise the temperature to 40°C, and stir to react for 4-5 hours to obtain a functional monomer c;
[0027] Further, the dosage ratio of the reaction product b and phenylalanine is 22-27 g: 0.1 mol;
[0028] During the reaction of step B2, the chlorine atom of the reaction product b reacts with the amino group of phenylalanine to undergo a dehydrochlorination reaction to generate a functional monomer c.
[0029] Step B3: Preparation of base material: Add methyl allyl polyoxyethylene ether and deionized water into a four-necked flask and stir for 20-30 minutes; Preparation of material A: Add acrylic acid and functional monomer c into deionized water and stir for 15-25 minutes; Preparation of material B: Add ascorbic acid and thioglycolic acid into deionized water and stir for 15-25 minutes; Add hydrogen peroxide into the base material, and after 2 minutes, slowly add materials A and B at the same time; Add materials A and B for 3 hours, and keep warm for 1.5 hours after adding; Add sodium hydroxide solution into the four-necked flask after cooling, and adjust its pH value to 6-7 to obtain a modified water reducer;
[0030] Further, the dosage ratio of methyl allyl polyoxyethylene ether, deionized water and hydrogen peroxide in the base material is 0.1 mol: 120-150 mL: 0.02-0.04 mol, the dosage ratio of acrylic acid, functional monomer c and deionized water in material A is 0.4 mol: 5-10 g: 150-180 mL, the dosage ratio of ascorbic acid, thioglycolic acid and deionized water in material B is 0.03 mol: 0.015-0.025 mol: 80-100 mL, the mass fraction of hydrogen peroxide is 30%, and the mass fraction of sodium hydroxide solution is 30%;
[0031] During the reaction of step B3, methyl allyl polyoxyethylene ether, acrylic acid and functional monomer c undergo polymerization reaction to generate a modified water reducing agent.
[0032] Beneficial effects of the invention: The invention discloses a modified cement slurry composite additive for mining, a preparation method and an application thereof. The modified cement slurry composite additive for mining comprises the following components: modified water reducing agent, bentonite, polyaluminum sulfate, polyaluminum chloride, calcium sulfate, hydroxypropyl methylcellulose, modified microcapsules and water.
[0033] The modified microcapsules are obtained by coating toluene diisocyanate with modified polypropylene, and the modified polypropylene contains hydroxyl, benzotriazole, and polysiloxane chains; the introduction of the hydrophilic group hydroxyl improves the hydrophilicity of the polypropylene surface, so that the dispersibility of the modified microcapsules in the cement slurry is enhanced; the hydroxyl group and the nitrogen atom on the benzotriazole ring form a six-membered chelate ring through intramolecular hydrogen bonding to exert the ultraviolet absorption function, and based on the tautomerism in the compound molecule, the absorbed ultraviolet energy is converted into other forms of energy release to protect the matrix from ultraviolet damage, thereby improving the modified polypropylene. The anti-ultraviolet aging property is good; the Si-O-Si bond and Si-C bond contained in the polysiloxane chain have high bond energy and high energy required for breaking, which enhances the thermal stability of the modified polypropylene; the microcapsules formed by the modified polypropylene coated with toluene diisocyanate have good dispersibility in the cement slurry, high thermal stability and good anti-ultraviolet aging property, and are convenient for transportation and use, so that the modified microcapsules can stably play the role of improving the self-repairing ability of microcracks in the cement grouting material and improving the durability of the cement grouting material, thereby enhancing the self-healing ability of the cement grouting material prepared using the composite additive.
[0034] The synthesized modified water-reducing agent is obtained by introducing polysiloxane chains and phenylalanine into polycarboxylic acid water-reducing agent; the polysiloxane chain has excellent thermal stability, which improves the thermal stability of the modified water-reducing agent and makes it more suitable for the use of cement slurry in the high-temperature environment of mines, so the dispersibility and dispersion retention of the modified water-reducing agent on the cement slurry are improved; an amino acid with a benzene ring structure is introduced into the end of the reaction product a, i.e., maleic anhydride monool ester, to reduce the hydrogen bonding between the polyoxyethylene side chain and the montmorillonite layer by utilizing the rigid hydrophobic structure of the benzene ring, and the amino acid modification The end of the monomer carries a negatively charged carboxyl group, which can form an electrostatic repulsion with the negatively charged layer of montmorillonite, thereby reducing intercalation adsorption. Combined with the steric hindrance effect of the phenylalanine end, the intercalation adsorption resistance is further increased, while reducing the adsorption on the surface of montmorillonite, so that the modified water-reducing agent has a higher anti-adsorption capacity for montmorillonite; using the modified water-reducing agent with both water-reducing and mud-resistant properties, a cement slurry with better dispersibility and mud-resistance can be obtained at a low dosage, so that the performance of the obtained cement grouting material is better, and the compressive strength of the cement grouting material made of the composite additive is enhanced. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1: A modified microcapsule, the preparation of which comprises the following steps:
[0037] Step A1: 4-bromo-2-nitroaniline, concentrated hydrochloric acid and water were added to a flask, stirred at 30°C for 30 minutes, and then cooled to 0°C in an ice-water bath. Sodium nitrite solution was slowly added dropwise to the flask, and the reaction was stirred for 20 minutes to obtain a reaction solution. Urea was added until the reaction solution turned starch-potassium iodide test paper blue to obtain a diazonium salt intermediate. Then, isoeugenol and methanol were added to a three-necked flask, sodium carbonate was added to adjust the pH to 7.5, and the diazonium salt intermediate was slowly added under stirring in an ice-water bath at 4 The addition was completed within 5 minutes, and the reaction was continued with stirring for 2 hours to obtain a diazo product; the dosage ratio of 4-bromo-2-nitroaniline, concentrated hydrochloric acid, water, and sodium nitrite solution was 0.032 mol: 8 mL: 4 mL: 45 mL, the mass fraction of concentrated hydrochloric acid was 36.5%, and the concentration of sodium nitrite solution was 1 mol / L; the dosage ratio of isoeugenol, methanol, sodium carbonate, and diazonium salt intermediate was 0.016 mol: 80 mL: 0.005 mol: 0.016 mol;
[0038] Step A2: Add the diazo product, ethanol and sodium hydroxide into a three-necked flask, heat to 65°C, start reflux stirring, then add an equal amount of sodium dithionite three times, reflux stirring and react for 1 hour, cool to room temperature, add hydrochloric acid to adjust the pH to 5, filter, wash the filter cake with anhydrous ethanol, and dry to obtain brominated aromatic hydrocarbons; the dosage ratio of the diazo product, ethanol, sodium hydroxide and sodium dithionite is 0.1 mol: 115 mL: 0.02 mol: 0.2 mol; the volume fraction of ethanol is 95%;
[0039] Step A3: Add bromoaryl hydrocarbon, 3-aminopropylpentamethyldisiloxane and methanol into a flask, add 2-dicyclohexylphospho-2'-4'-6'-triisopropylbiphenyl, tris(dibenzylideneacetone)dipalladium and potassium carbonate, reflux and stir at 80°C under nitrogen protection for 4 hours, and vacuum dry at 50°C to obtain a functional monomer; the amount ratio of bromoaryl hydrocarbon, 3-aminopropylpentamethyldisiloxane, methanol, 2-dicyclohexylphospho-2'-4'-6'-triisopropylbiphenyl, tris(dibenzylideneacetone)dipalladium and potassium carbonate is 0.12 mol: 0.06 mol: 135 mL: 0.0025 g: 0.0025 g: 0.15 mol;
[0040] Step A4: In a nitrogen atmosphere, toluene, functional monomers and crosslinking agents were added to the reaction bottle, stirred for 10 min, polypropylene was added and stirred for another 10 min, the reaction bottle was sealed, and then 60 After irradiation with Coγ-rays for 8 hours, the polypropylene is taken out, and the taken out polypropylene is rinsed with anhydrous ethanol, extracted with acetone, and dried to obtain modified polypropylene; the modified polypropylene is placed in a flask and heated to 160°C, stirred for 30 minutes, and then toluene diisocyanate is added, the temperature is maintained at 160°C, and stirring is continued for 2 hours, and then perfluorotributylamine is quickly added at a stirring speed of 600r / min and cooled to obtain a suspension, the suspension is dispersed with ultrasound for 30 minutes, filtered, and placed in a 60°C oven for drying for 24 hours to obtain modified microcapsules; the amount ratio of toluene, functional monomer, crosslinking agent, and polypropylene is 400mL:10g:7g:100g, and the crosslinking agent is divinylbenzene; the amount ratio of modified polypropylene, toluene diisocyanate, and perfluorotributylamine is 10g:20g:15g.
[0041] Embodiment 2: A modified microcapsule, the preparation of which comprises the following steps:
[0042] Step A1: 4-bromo-2-nitroaniline, concentrated hydrochloric acid and water were added to a flask, stirred at 30°C for 30 minutes, and then cooled to 0°C in an ice-water bath. Sodium nitrite solution was slowly added dropwise to the flask, and the reaction was stirred for 25 minutes to obtain a reaction solution. Urea was added until the reaction solution turned starch-potassium iodide paper blue to obtain a diazonium salt intermediate. Then, isoeugenol and methanol were added to a three-necked flask, sodium carbonate was added to adjust the pH to 8.0, and the diazonium salt intermediate was slowly added under stirring in an ice-water bath at 52 °C. The addition was completed within 10 minutes, and the reaction was continued with stirring for 2.3 hours to obtain a diazo product; the dosage ratio of 4-bromo-2-nitroaniline, concentrated hydrochloric acid, water, and sodium nitrite solution was 0.032 mol: 8 mL: 4 mL: 50 mL, the mass fraction of concentrated hydrochloric acid was 36.5%, and the concentration of sodium nitrite solution was 1 mol / L; the dosage ratio of isoeugenol, methanol, sodium carbonate, and diazonium salt intermediate was 0.016 mol: 85 mL: 0.008 mol: 0.016 mol;
[0043] Step A2: Add the diazo product, ethanol and sodium hydroxide into a three-necked flask, heat to 70°C, start reflux stirring, then add an equal amount of sodium dithionite three times, reflux stirring and react for 1.3 hours, cool to room temperature, add hydrochloric acid to adjust the pH to 5.5, filter, wash the filter cake with anhydrous ethanol, and dry to obtain brominated aromatic hydrocarbons; the dosage ratio of the diazo product, ethanol, sodium hydroxide and sodium dithionite is 0.1 mol: 120 mL: 0.03 mol: 0.25 mol; the volume fraction of ethanol is 95%;
[0044] Step A3: Add bromoaryl hydrocarbon, 3-aminopropylpentamethyldisiloxane and methanol into a flask, add 2-dicyclohexylphospho-2'-4'-6'-triisopropylbiphenyl, tris(dibenzylideneacetone)dipalladium and potassium carbonate, reflux and stir at 80°C under nitrogen protection for 4.5 hours, and vacuum dry at 50°C to obtain a functional monomer; the amount ratio of bromoaryl hydrocarbon, 3-aminopropylpentamethyldisiloxane, methanol, 2-dicyclohexylphospho-2'-4'-6'-triisopropylbiphenyl, tris(dibenzylideneacetone)dipalladium and potassium carbonate is 0.12 mol: 0.06 mol: 140 mL: 0.0025 g: 0.0025 g: 0.16 mol;
[0045] Step A4: In a nitrogen atmosphere, toluene, functional monomers and crosslinking agents were added to the reaction bottle, stirred for 10-15 minutes, polypropylene was added and stirred for 13 minutes, and the reaction bottle was sealed and then 60After irradiation with Coγ-rays for 9 hours, the polypropylene was taken out, and the polypropylene was rinsed with anhydrous ethanol, extracted with acetone, and dried to obtain modified polypropylene; the modified polypropylene was placed in a flask and heated to 160°C, stirred for 30 minutes, and then toluene diisocyanate was added, the temperature was maintained at 160°C, and stirring was continued for 2 hours, and then perfluorotributylamine was quickly added at a stirring speed of 600r / min and cooled to obtain a suspension, the suspension was dispersed with ultrasound for 30 minutes, filtered, and placed in a 60°C oven for drying for 24 hours to obtain modified microcapsules; the amount ratio of toluene, functional monomer, crosslinking agent, and polypropylene was 430mL:13g:8g:105g, and the crosslinking agent was divinylbenzene; the amount ratio of modified polypropylene, toluene diisocyanate, and perfluorotributylamine was 13g:25g:20g.
[0046] Embodiment 3: A modified microcapsule, the preparation of which comprises the following steps:
[0047] Step A1: 4-bromo-2-nitroaniline, concentrated hydrochloric acid and water were added to a flask, stirred at 30°C for 30 minutes, and then cooled to 0°C in an ice-water bath. Sodium nitrite solution was slowly added dropwise to the flask, and the reaction was stirred for 30 minutes to obtain a reaction solution. Urea was added until the reaction solution turned starch-potassium iodide test paper blue to obtain a diazonium salt intermediate. Then, isoeugenol and methanol were added to a three-necked flask, sodium carbonate was added to adjust the pH to 8.5, and the diazonium salt intermediate was slowly added under stirring in an ice-water bath at 60°C. The addition was completed within 10 minutes, and the reaction was continued with stirring for 2.5 hours to obtain a diazo product; the dosage ratio of 4-bromo-2-nitroaniline, concentrated hydrochloric acid, water, and sodium nitrite solution was 0.032 mol: 8 mL: 4 mL: 55 mL, the mass fraction of concentrated hydrochloric acid was 36.5%, and the concentration of sodium nitrite solution was 1 mol / L; the dosage ratio of isoeugenol, methanol, sodium carbonate, and diazonium salt intermediate was 0.016 mol: 90 mL: 0.010 mol: 0.016 mol;
[0048] Step A2: Add the diazo product, ethanol and sodium hydroxide into a three-necked flask, heat to 75°C, start reflux stirring, then add an equal amount of sodium dithionite three times, reflux stirring and react for 1.5 hours, cool to room temperature, add hydrochloric acid to adjust the pH to 6, filter, wash the filter cake with anhydrous ethanol, and dry to obtain brominated aromatic hydrocarbons; the dosage ratio of the diazo product, ethanol, sodium hydroxide and sodium dithionite is 0.1 mol: 125 mL: 0.05 mol: 0.3 mol; the volume fraction of ethanol is 95%;
[0049] Step A3: Add bromoaryl hydrocarbon, 3-aminopropylpentamethyldisiloxane and methanol into a flask, add 2-dicyclohexylphospho-2'-4'-6'-triisopropylbiphenyl, tris(dibenzylideneacetone)dipalladium and potassium carbonate, reflux and stir at 80°C under nitrogen protection for 5 hours, and vacuum dry at 50°C to obtain a functional monomer; the amount ratio of bromoaryl hydrocarbon, 3-aminopropylpentamethyldisiloxane, methanol, 2-dicyclohexylphospho-2'-4'-6'-triisopropylbiphenyl, tris(dibenzylideneacetone)dipalladium and potassium carbonate is 0.12 mol: 0.06 mol: 145 mL: 0.0025 g: 0.0025 g: 0.18 mol;
[0050] Step A4: In a nitrogen atmosphere, toluene, functional monomers and crosslinking agents were added to the reaction bottle, and after stirring for 15 min, polypropylene was added and stirred for another 15 min. The reaction bottle was sealed and then 60 After irradiation with Coγ-rays for 10 hours, the polypropylene is taken out, and the taken out polypropylene is rinsed with anhydrous ethanol, extracted with acetone, and dried to obtain modified polypropylene; the modified polypropylene is placed in a flask and heated to 160°C, stirred for 30 minutes, and then toluene diisocyanate is added, the temperature is maintained at 160°C, and stirring is continued for 2 hours, and then perfluorotributylamine is quickly added at a stirring speed of 600r / min and cooled to obtain a suspension, the suspension is dispersed with ultrasound for 30 minutes, filtered, and placed in a 60°C oven for drying for 24 hours to obtain modified microcapsules; the amount ratio of toluene, functional monomer, crosslinking agent, and polypropylene is 450mL:15g:9g:110g, and the crosslinking agent is divinylbenzene; the amount ratio of modified polypropylene, toluene diisocyanate, and perfluorotributylamine is 15g:30g:25g.
[0051] Embodiment 4: A modified water reducing agent, the preparation of which comprises the following steps:
[0052] Step B1: Add dihydroxy-terminated polydimethylsiloxane to a flask, introduce nitrogen, heat to 70°C, stir for 30 minutes, then add hydroquinone, triethylamine and maleic anhydride, heat to 80°C, stir for 4 hours, and obtain reaction product a; in a nitrogen atmosphere, add reaction product a to a round-bottom flask, heat to 45°C, add tetrabutylammonium bromide, start stirring, slowly drop epichlorohydrin into the round-bottom flask, stir and react for 5 hours, and obtain reaction product b; the amount ratio of dihydroxy-terminated polydimethylsiloxane, hydroquinone, triethylamine and maleic anhydride is 50g:0.04g:2.49g:19.6g; the amount ratio of reaction product a, tetrabutylammonium bromide and epichlorohydrin is 20g:0.001mol:0.1mol;
[0053] Step B2: In a nitrogen atmosphere, add the reaction product b and phenylalanine into a flask, raise the temperature to 40°C, and stir to react for 4 hours to obtain a functional monomer c; the amount ratio of the reaction product b and phenylalanine is 22g:0.1mol;
[0054] Step B3: Preparation of base material: Add methyl allyl polyoxyethylene ether and deionized water into a four-necked flask and stir for 20 minutes; Preparation of material A: Add acrylic acid and functional monomer c into deionized water and stir for 15 minutes; Preparation of material B: Add ascorbic acid and thioglycolic acid into deionized water and stir for 15 minutes; Add hydrogen peroxide to the base material, and after 2 minutes, slowly add materials A and B at the same time; Add materials A and B for 3 hours, and keep warm for 1.5 hours after adding; After cooling, add sodium hydroxide solution into the four-necked flask, The pH value is adjusted to 6 to obtain a modified water-reducing agent; the dosage ratio of methyl allyl polyoxyethylene ether, deionized water and hydrogen peroxide in the base material is 0.1 mol: 120 mL: 0.02 mol, the dosage ratio of acrylic acid, functional monomer c and deionized water in material A is 0.4 mol: 5 g: 150 mL, the dosage ratio of ascorbic acid, thioglycolic acid and deionized water in material B is 0.03 mol: 0.015 mol: 80 mL, the mass fraction of hydrogen peroxide is 30%, and the mass fraction of sodium hydroxide solution is 30%.
[0055] Embodiment 5: A modified water reducing agent, the preparation of which comprises the following steps:
[0056] Step B1: Add bishydroxy-terminated polydimethylsiloxane to a flask, introduce nitrogen, heat to 75°C, stir for 30 minutes, then add hydroquinone, triethylamine and maleic anhydride, heat to 85°C, stir for 4.5 hours to obtain reaction product a; in a nitrogen atmosphere, add reaction product a to a round-bottom flask, heat to 45°C, add tetrabutylammonium bromide, start stirring, slowly drop epichlorohydrin into the round-bottom flask, stir and react for 5.5 hours to obtain reaction product b; the amount ratio of bishydroxy-terminated polydimethylsiloxane, hydroquinone, triethylamine and maleic anhydride is 50g:0.04g:2.49g:19.6g; the amount ratio of reaction product a, tetrabutylammonium bromide and epichlorohydrin is 23g:0.0011mol:0.1mol;
[0057] Step B2: In a nitrogen atmosphere, add the reaction product b and phenylalanine into a flask, raise the temperature to 40°C, and stir to react for 4.5 hours to obtain a functional monomer c; the amount ratio of the reaction product b and phenylalanine is 25g:0.1mol;
[0058] Step B3: Preparation of base material: Add methyl allyl polyoxyethylene ether and deionized water into a four-necked flask and stir for 25 minutes; Preparation of material A: Add acrylic acid and functional monomer c into deionized water and stir for 20 minutes; Preparation of material B: Add ascorbic acid and thioglycolic acid into deionized water and stir for 20 minutes; Add hydrogen peroxide to the base material, and after 2 minutes, slowly add material A and material B at the same time; Add material A and material B for 3 hours, and keep warm for 1.5 hours after adding; After cooling, add sodium hydroxide solution into the four-necked flask and The pH value is adjusted to 6.5 to obtain a modified water-reducing agent; the dosage ratio of methyl allyl polyoxyethylene ether, deionized water and hydrogen peroxide in the base material is 0.1 mol: 135 mL: 0.03 mol, the dosage ratio of acrylic acid, functional monomer c and deionized water in material A is 0.4 mol: 8 g: 165 mL, the dosage ratio of ascorbic acid, thioglycolic acid and deionized water in material B is 0.03 mol: 0.020 mol: 90 mL, the mass fraction of hydrogen peroxide is 30%, and the mass fraction of sodium hydroxide solution is 30%.
[0059] Embodiment 6: A modified water reducing agent, the preparation of which comprises the following steps:
[0060] Step B1: Add bishydroxy-terminated polydimethylsiloxane to a flask, introduce nitrogen, heat to 80°C, stir for 30 minutes, then add hydroquinone, triethylamine and maleic anhydride, heat to 90°C, stir for 5 hours, and obtain reaction product a; in a nitrogen atmosphere, add reaction product a to a round-bottom flask, heat to 45°C, add tetrabutylammonium bromide, start stirring, slowly drop epichlorohydrin into the round-bottom flask, stir and react for 6 hours, and obtain reaction product b; the amount ratio of bishydroxy-terminated polydimethylsiloxane, hydroquinone, triethylamine and maleic anhydride is 50g:0.04g:2.49g:19.6g; the amount ratio of reaction product a, tetrabutylammonium bromide and epichlorohydrin is 25g:0.0012mol:0.1mol;
[0061] Step B2: In a nitrogen atmosphere, add the reaction product b and phenylalanine into a flask, raise the temperature to 40°C, and stir to react for 5 hours to obtain a functional monomer c; the amount ratio of the reaction product b and phenylalanine is 27g:0.1mol;
[0062] Step B3: Preparation of base material: Add methyl allyl polyoxyethylene ether and deionized water into a four-necked flask and stir for 30 minutes; Preparation of material A: Add acrylic acid and functional monomer c into deionized water and stir for 25 minutes; Preparation of material B: Add ascorbic acid and thioglycolic acid into deionized water and stir for 25 minutes; Add hydrogen peroxide to the base material, and after 2 minutes, slowly add materials A and B at the same time; Add materials A and B for 3 hours, and keep warm for 1.5 hours after adding; After cooling, add sodium hydroxide solution into the four-necked flask and The pH value is adjusted to 7 to obtain a modified water-reducing agent; the dosage ratio of methyl allyl polyoxyethylene ether, deionized water and hydrogen peroxide in the base material is 0.1 mol: 150 mL: 0.04 mol, the dosage ratio of acrylic acid, functional monomer c and deionized water in material A is 0.4 mol: 10 g: 180 mL, the dosage ratio of ascorbic acid, thioglycolic acid and deionized water in material B is 0.03 mol: 0.025 mol: 100 mL, the mass fraction of hydrogen peroxide is 30%, and the mass fraction of sodium hydroxide solution is 30%.
[0063] Example 7: A modified cement slurry composite additive for mining, comprising the following components in parts by weight: 2 parts of modified water reducing agent, 4 parts of bentonite, 1 part of polyaluminum sulfate, 0.5 parts of polyaluminum chloride, 4 parts of calcium sulfate, 0.5 parts of hydroxypropyl methylcellulose, 0.6 parts of modified microcapsules, and 25 parts of water;
[0064] The preparation of the modified cement slurry composite additive for mining comprises the following steps:
[0065] The modified water reducing agent obtained in Example 4, bentonite, polyaluminum sulfate, polyaluminum chloride, calcium sulfate, hydroxypropyl methylcellulose, and the modified microcapsules obtained in Example 1 were sequentially added into water and stirred for 20 minutes to obtain a modified cement slurry composite additive for mining.
[0066] The application of the modified cement slurry composite additive for mining is as follows: 100 parts of silicate cement, 30 parts of the modified cement slurry composite additive for mining and 60 parts of water are stirred for 30 minutes, and then injected into the rock fissures in the mine shaft by single-liquid grouting with a grouting pressure of 0.6 MPa, so as to be used for the reinforcement and treatment of the rock fissures in the mine shaft.
[0067] Example 8: A modified cement slurry composite additive for mining, comprising the following components in parts by weight: 3 parts of modified water reducing agent, 5 parts of bentonite, 1.5 parts of polyaluminum sulfate, 0.8 parts of polyaluminum chloride, 5 parts of calcium sulfate, 0.6 parts of hydroxypropyl methylcellulose, 0.7 parts of modified microcapsules, and 30 parts of water;
[0068] The preparation of the modified cement slurry composite additive for mining comprises the following steps:
[0069] The modified water reducing agent obtained in Example 5, bentonite, polyaluminum sulfate, polyaluminum chloride, calcium sulfate, hydroxypropyl methylcellulose, and the modified microcapsules obtained in Example 2 were sequentially added into water and stirred for 25 minutes to obtain a modified cement slurry composite additive for mining.
[0070] Application of the modified cement slurry composite additive for mining: 100 parts of silicate cement, 33 parts of the modified cement slurry composite additive for mining and 63 parts of water are stirred for 35 minutes, and then injected into the rock fissures in the mine shaft by single-liquid grouting with a grouting pressure of 0.7 MPa, so as to be used for the reinforcement and treatment of the rock fissures in the mine shaft.
[0071] Example 9: A modified cement slurry composite additive for mining, comprising the following components in parts by weight: 4 parts of modified water reducing agent, 6 parts of bentonite, 2 parts of polyaluminum sulfate, 1 part of polyaluminum chloride, 6 parts of calcium sulfate, 0.7 parts of hydroxypropyl methylcellulose, 0.8 parts of modified microcapsules, and 35 parts of water;
[0072] The preparation of the modified cement slurry composite additive for mining comprises the following steps:
[0073] The modified water reducing agent obtained in Example 6, bentonite, polyaluminum sulfate, polyaluminum chloride, calcium sulfate, hydroxypropyl methylcellulose, and the modified microcapsules obtained in Example 3 were sequentially added into water and stirred for 30 minutes to obtain a modified cement slurry composite additive for mining.
[0074] The application of the modified cement slurry composite additive for mining is as follows: 100 parts of silicate cement, 35 parts of the modified cement slurry composite additive for mining and 65 parts of water are stirred for 40 minutes, and then injected into the rock fissures in the mine shaft by single-liquid grouting with a grouting pressure of 0.8 MPa, so as to be used for the reinforcement and treatment of the rock fissures in the mine shaft.
[0075] Comparative Example 1: Compared with Example 9, the modified polypropylene used in the preparation process of the modified microcapsules obtained in Example 3 was replaced with polypropylene to obtain a modified cement slurry composite additive for mining.
[0076] Comparative Example 2: Compared with Example 9, the functional monomer c used in the preparation process of the modified water-reducing agent obtained in Example 6 is replaced with the reaction product b to obtain a modified cement slurry composite additive for mining.
[0077] The effect of the modified cement slurry composite additive for mining prepared by the present invention is further tested, and the test results are as follows.
[0078] In order to test the performance of the modified cement slurry composite additive for mining prepared by the present invention, the modified cement slurry composite additive for mining obtained in Examples 7-9 and Comparative Examples 1-2 was stirred and mixed with silicate cement and water according to the proportion of the modified cement slurry composite additive for mining used for reinforcement and treatment of rock mass fissures in mines, poured into a mold with a size of 70 mm × 70 mm × 70 mm, immediately covered with a waterproof film after molding, and moved into a standard curing room (20 ± 2 ° C, 95% relative humidity) for 28 days to obtain a sample to be tested; the splitting method was used Crack prefabrication was performed. During the crack prefabrication process, the specimens were loaded using a fully automatic flexural and compressive testing machine, and the initial width of the cracks on the surface of the specimens was measured using a crack comprehensive analysis tester. After the specimens with a prefabricated crack width of 0.23 mm were subjected to standard curing, the time required for the surface cracks to heal was measured to evaluate the self-healing ability of the microcapsules on the surface cracks of cement-based materials. The compressive strength of the samples to be tested was determined according to GB / T17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)", and the results are recorded in Table 1.
[0079] Table 1: Test results
[0080]
[0081] According to the data in Table 1, the modified cement slurry composite additive for mining prepared by the present invention has high high temperature resistance, crack self-healing ability and compressive strength. Comparison between Example 9 and Comparative Example 1 shows that the composite additive prepared by using modified microcapsules made of modified polypropylene with good dispersibility, thermal stability and UV aging resistance has better dispersibility, thermal stability and aging resistance in cement slurry, and thus the obtained cement slurry has better high temperature resistance and stronger crack self-healing ability. Comparison between Example 9 and Comparative Example 2 shows that the modified water reducer introduced with phenylalanine has good anti-mud performance, enhances the dispersibility of cement slurry, and thus improves the compressive strength of cement slurry.
[0082] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A composite additive for modified cement slurry for mining, characterized in that: The invention comprises the following components in parts by weight: 2-4 parts of modified water reducing agent, 4-6 parts of bentonite, 1-2 parts of polyaluminium sulfate, 0.5-1 parts of polyaluminium chloride, 4-6 parts of calcium sulfate, 0.5-0.7 parts of hydroxypropyl methylcellulose, 0.6-0.8 parts of modified microcapsules and 25-35 parts of water; The modified microcapsules are prepared by the following steps: Step A1: 4-bromo-2-nitroaniline, concentrated hydrochloric acid and water are added to a flask, stirred at 30°C for 30 minutes, and then cooled to 0°C in an ice-water bath. Sodium nitrite solution is slowly added dropwise to the flask, and the reaction is stirred for 20-30 minutes to obtain a reaction solution, and urea is added until the reaction solution turns starch-potassium iodide test paper blue to obtain a diazonium salt intermediate; isoeugenol and methanol are then added to a three-necked flask, and sodium carbonate is added to adjust the pH to 7.5-8.
5. The diazonium salt intermediate is slowly added dropwise within 45-60 minutes while stirring in an ice-water bath, and the reaction is continued with stirring for 2-2.5 hours to obtain a diazo product; Step A2: Add the diazo product, ethanol and sodium hydroxide into a three-necked flask, heat to 65-75°C, start reflux stirring, then add an equal amount of sodium dithionite three times, reflux stirring and react for 1-1.5h, cool to room temperature, add hydrochloric acid to adjust the pH to 5-6, filter, wash the filter cake with anhydrous ethanol, and dry to obtain bromoaryl hydrocarbon; Step A3: Add bromoaryl hydrocarbon, 3-aminopropylpentamethyldisiloxane and methanol into a flask, add 2-dicyclohexylphosphine-2'-4'-6'-triisopropylbiphenyl, tris(dibenzylideneacetone)dipalladium and potassium carbonate, reflux and stir at 80°C under nitrogen protection for 4-5h, and vacuum dry at 50°C to obtain a functional monomer; Step A4: In a nitrogen atmosphere, toluene, functional monomers and crosslinking agents were added to the reaction bottle, and after stirring for 10-15 minutes, polypropylene was added and stirred for another 10-15 minutes. The reaction bottle was sealed and then 60 After irradiating with Coγ-rays for 8-10 hours, the polypropylene is taken out, and the taken out polypropylene is rinsed with anhydrous ethanol, extracted with acetone, and dried to obtain modified polypropylene; the modified polypropylene is placed in a flask and heated to 160°C, stirred for 30 minutes, and then toluene diisocyanate is added, the temperature is maintained at 160°C, and stirring is continued for 2 hours, and then perfluorotributylamine is quickly added at a stirring speed of 600r / min and cooled to obtain a suspension, the suspension is dispersed with ultrasound for 30 minutes, filtered, and placed in a 60°C oven for drying for 24 hours to obtain modified microcapsules.
2. The modified cement slurry composite additive for mining according to claim 1, characterized in that: In step A1, the dosage ratio of 4-bromo-2-nitroaniline, concentrated hydrochloric acid, water, and sodium nitrite solution is 0.032 mol: 8 mL: 4 mL: 45-55 mL, the mass fraction of concentrated hydrochloric acid is 36.5%, and the concentration of sodium nitrite solution is 1 mol / L; the dosage ratio of isoeugenol, methanol, sodium carbonate, and diazonium salt intermediate is 0.016 mol: 80-90 mL: 0.005-0.010 mol: 0.016 mol.
3. The modified cement slurry composite additive for mining according to claim 1, characterized in that: In step A2, the dosage ratio of the diazo product, ethanol, sodium hydroxide and sodium dithionite is 0.1 mol: 115-125 mL: 0.02-0.05 mol: 0.2-0.3 mol, and the volume fraction of ethanol is 95%; in step A3, the dosage ratio of bromoaryl hydrocarbon, 3-aminopropylpentamethyldisiloxane, methanol, 2-dicyclohexylphospho-2'-4'-6'-triisopropylbiphenyl, tris(dibenzylideneacetone)dipalladium and potassium carbonate is 0.12 mol: 0.06 mol: 135-145 mL: 0.0025 g: 0.0025 g: 0.15-0.18 mol.
4. The modified cement slurry composite additive for mining according to claim 1, characterized in that: In step A4, the usage ratio of toluene, functional monomer, cross-linking agent and polypropylene is 400-450mL: 10-15g: 7-9g: 100-110g, and the cross-linking agent is divinylbenzene; the usage ratio of modified polypropylene, toluene diisocyanate and perfluorotributylamine is 10-15g: 20-30g: 15-25g.
5. The modified cement slurry composite additive for mining according to claim 1, characterized in that: The modified water-reducing agent is prepared by the following steps: Step B1: Add dihydroxy-terminated polydimethylsiloxane to a flask, introduce nitrogen, heat to 70-80°C, stir for 30 minutes, then add hydroquinone, triethylamine and maleic anhydride, heat to 80-90°C, stir for 4-5 hours, and obtain reaction product a; In a nitrogen atmosphere, add reaction product a to a round-bottom flask, heat to 45°C, add tetrabutylammonium bromide, start stirring, slowly add epichlorohydrin dropwise to the round-bottom flask, stir and react for 5-6 hours, and obtain reaction product b; Step B2: In a nitrogen atmosphere, add the reaction product b and phenylalanine into a flask, raise the temperature to 40°C, and stir to react for 4-5 hours to obtain a functional monomer c; Step B3: Preparation of base material: Add methyl allyl polyoxyethylene ether and deionized water into a four-necked flask and stir for 20-30 minutes; Preparation of material A: Add acrylic acid and functional monomer c into deionized water and stir for 15-25 minutes; Preparation of material B: Add ascorbic acid and thioglycolic acid into deionized water and stir for 15-25 minutes; Add hydrogen peroxide into the base material, and after 2 minutes, slowly add materials A and B at the same time; Add materials A and B for 3 hours, and keep warm for 1.5 hours after adding; Add sodium hydroxide solution into the four-necked flask after cooling, and adjust its pH value to 6-7 to obtain the modified water reducer.
6. The modified cement slurry composite additive for mining according to claim 5, characterized in that: In step B1, the usage ratio of bishydroxy-terminated polydimethylsiloxane, hydroquinone, triethylamine and maleic anhydride is 50g:0.04g:2.49g:19.6g; the usage ratio of reaction product a, tetrabutylammonium bromide and epichlorohydrin is 20-25g:0.001-0.0012mol:0.1mol.
7. The modified cement slurry composite additive for mining according to claim 5, characterized in that: In step B2, the usage ratio of reaction product b and phenylalanine is 22-27 g:0.1 mol.
8. The modified cement slurry composite additive for mining according to claim 5, characterized in that: In step B3, the dosage ratio of methyl allyl polyoxyethylene ether, deionized water and hydrogen peroxide in the base material is 0.1 mol: 120-150 mL: 0.02-0.04 mol, the dosage ratio of acrylic acid, functional monomer c and deionized water in material A is 0.4 mol: 5-10 g: 150-180 mL, the dosage ratio of ascorbic acid, thioglycolic acid and deionized water in material B is 0.03 mol: 0.015-0.025 mol: 80-100 mL, the mass fraction of hydrogen peroxide is 30%, and the mass fraction of sodium hydroxide solution is 30%.
9. The method for preparing a composite additive for modified cement slurry for mining according to claim 1, characterized in that: The steps include: Add modified water reducing agent, bentonite, polyaluminum sulfate, polyaluminum chloride, calcium sulfate, hydroxypropyl methylcellulose and modified microcapsules into water in sequence and stir for 20-30 minutes to obtain a composite additive for modified cement slurry for mining.
10. The use of a composite additive for modified cement slurry for mining according to claim 1, characterized in that: After mixing 100 parts of silicate cement, 30-35 parts of mining modified cement slurry composite additives and 60-65 parts of water for 30-40 minutes, single-liquid grouting with a grouting pressure of 0.6-0.8MPa is used to reinforce the rock cracks in the mine.
Citation Information
Patent Citations
Concrete curing agent and preparation method thereof
CN112778022A
Consumer product with controlled release, biodegradable core-shell microcapsule compositions
CN113950315A